2023
DOI: 10.3390/toxics11030239
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans as a Prediction Platform for Nanotechnology-Based Strategies: Insights on Analytical Challenges

Abstract: Nanotechnology-based strategies have played a pivotal role in innovative products in different technological fields, including medicine, agriculture, and engineering. The redesign of the nanometric scale has improved drug targeting and delivery, diagnosis, water treatment, and analytical methods. Although efficiency brings benefits, toxicity in organisms and the environment is a concern, particularly in light of global climate change and plastic disposal in the environment. Therefore, to measure such effects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 195 publications
0
1
0
Order By: Relevance
“…elegans are nematodes which can grow up to 1 mm in size in its fully developed adult stage. They are often used for understanding nanotoxicity through oral uptake which is also the major form of nanotoxicity in human beings [133][134][135][136][137][138]. They pose around 70-80% of gene homology with humans and have around 70% of major signal transduction pathways conserved as compared to human beings.…”
Section: Elegansmentioning
confidence: 99%
“…elegans are nematodes which can grow up to 1 mm in size in its fully developed adult stage. They are often used for understanding nanotoxicity through oral uptake which is also the major form of nanotoxicity in human beings [133][134][135][136][137][138]. They pose around 70-80% of gene homology with humans and have around 70% of major signal transduction pathways conserved as compared to human beings.…”
Section: Elegansmentioning
confidence: 99%
“…Its simple structure, easy laboratory cultivation, low cost, simple experimental operation, short growth cycle, multiple offspring production, well-defined genetic background, and variable meiotic behavior give it inherent advantages in the study of germline cells [15]. Notably, genetic sequencing of C. elegans revealed that 60-80% of its genes are homologous to those of humans [14][15][16][17]. Furthermore, C. elegans is used as a sensitive bioindicator in various exposure media (soil, water, and sediment) used in toxicological studies to observe different toxicological endpoints, such as mortality, reproductive toxicity, and behavioral changes [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%